关于房产税立法的三大基本问题 - 张守文 (税务研究, 2012)
探讨房产税立法的三大基本问题,有助于明晰立法的目标,基础和制度架构,确保立法的合法性和合理性;房产税立法同样应遵循法定,公平和效率三大基本原则,这有助于解决授权立法和立法模式选择等问题;应适度估价房产税的制度功用,把握立法时机和立法成本,全面推进整体的房产税制度建设.Discussing?the?three?fundamental?issues?in?the?legislation?of?property?tax?is?conductive?to?clearly-set?goals,?foundation?and?system?structuring?of?legislation?and?as?well?as?to?ensure?legality?and?rationality.?In?the?process?of?legislation?of?property?tax,?the?three?basic?principles,?such?as?legal?nature,?equity?and?efficiency,?should?be?abided?by?to?solve?the?problems?resulting?from?delegated?legislation?and?legislative?mode?selection.?To?promote?the?integrated?systematic?construction?in?property?tax?legislation?in?an?all-round?manner?and?to?seize?the?legislating?opportunity?and?control?the?legislating?cost,?the?systematic?function?of?property?tax?legislation?shall?be?evaluated?appropriately.
Keywords: 房产税; 立法目的; 立法依据; 立法模式; Property Tax; Goals in legislation; Foundation of legislation; Legislative mode